Analisis Struktur Biaya Usahatani Cengkeh Di Desa Raanan Baru Dua Kecamatan Motoling Barat Kabupaten Minahasa Selatan - Mamero, Putri; Laoh, Olly Esry Harryani; Montolalu, Maya Hendrietta (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the cost of cloves in Raanan Baru 2 Village, West Motoling District. Sampling in this study used the method (Purposive Sampling) or deliberately from clove farmers in Raanan Baru Dua Village, West Motoling District. The number of respondents was 10 people as respondents. The data used in this study are primary data and secondary data. Primary data was obtained by using direct interview techniques with clove farmers as respondents, by using a questionnaire (questionnaire) as an aid in data collection. While secondary data were obtained from the agencies involved in this study. The analytical method used in this research is cost analysis, analysis of total revenue and total income and the cost structure of farming. the results of research conducted on clove farming in Raanan Baru Dua Village, West Motoling District, obtained an income of Rp.93,906,348.- per harvest with a total income of IDR 196,790,000.- per harvest and a total cost of IDR 102,883,652.- per harvest of the total costs incurred fixed costs (Fix Cost) contributed to the total cost of 0.03 percent and variable costs (Variable Cost) contributed to the total cost of 99.96 percent and for the contribution of costs based on harvest preparation activities contributed to the total cost of 0.59 percent and for cost contributions based on harvest activities contributing to costs of 97.84 percent and for cost contributions based on post-harvest activities contributing to total costs of 1.16 percent.